USE OF MEDICINAL PLANTS FOR THE TREATMENT OF DIFFERENT SHEEP AND GOAT DISEASES IN THARPARKAR, SINDH, PAKISTAN - A. H. Mirani; K. B. Mirbahar; A. L. Bhutto; T. A. Qureshi (Pakistan Journal of Agriculture, Agricultural Engineering & Veterinary Sciences, 2014)
The current study was carried out to record the traditional use of medicinal plants being used for the treatment of different sheep and goat diseases in Tharparkar, Sindh, Pakistan. Using semi-structured open-ended questionnaire information was collected by interviewing respondents during May 2012 to April 2013. A total of 22 plant species of veterinary importance belonging to 17 botanical families were documented against 10 common diseases of sheep and goats. Brassica campestris was reported as the most frequently used plant, followed by Azadirachta indica and Plantago lanceolata. Brassicaceae followed by Apiaceae, Solanaceae and Amaryllidaceae were reported as the frequently used plant families. Ethnoveterinary knowledge is declining because of the rapid socio-economic changes and lack of interest of young people. It is a part of cultural heritage can be saved and propagated for future generation. The information is expected to be of value for veterinary practitioners as well as the herbal drug industry.